Utilization of Peatland Technology For Food Availability in a Legal Perspective - Kansil, Christine S.T.; Saly, Jeane Neltje; Tirayo, Adriel Michael (Jurnal Cita Hukum, 2019)
Abstract:     The results of this research revealed that problematics with the use of peat technology due to the rate of conversion of agricultural land, expansion of agricultural land, and increasing production of food crops is not optimal, despite long-term solutions to the crisis of fire and haze. Therefore, it is important to implement Government Regulation of 2016 about the Protection and Management of Peat Ecosystems to meet the basic needs of the community from local resources. The problem is what is the government’s effort to improve the realization of food sufficiency through the use of peatlands and what is the legal basis above that. The research methods use a normative juridical method, by used secondary data obtained through study literature and analysed qualitatively. The results and discussion of this research are that the government’s efforts in applying standard technology efficiently produce useful results with the use of peat as a solution to food security through a touch of technology. The legal basis is the Presidential Regulation of 2016 about Peat Restoration Agency, which functions to accelerate the restoration of the area and restore the hydrological functions of peat due to forest and land fires in a special, systematic, directed, integrated and comprehensive manner.Keywords: Food Availability, Peatlands, Technology Abstrak:Hasil penelitian ini mengungkapkan bahwa problematika dengan penggunaan teknologi gambut karena laju konversi lahan pertanian, perluasan lahan pertanian, dan peningkatan produksi tanaman pangan tidak optimal, meskipun solusi jangka panjang untuk krisis kebakaran dan kabut. Karena itu, penting untuk menerapkan Peraturan Pemerintah 2016 tentang Perlindungan dan Pengelolaan Ekosistem Gambut untuk memenuhi kebutuhan dasar masyarakat dari sumber daya lokal. Masalahnya adalah apa upaya pemerintah untuk meningkatkan realisasi kecukupan pangan melalui penggunaan lahan gambut dan apa dasar hukum di atas itu. Metode penelitian menggunakan metode yuridis normatif, dengan menggunakan data sekunder yang diperoleh melalui studi pustaka dan dianalisis secara kualitatif. Hasil dan diskusi dari penelitian ini adalah bahwa upaya pemerintah dalam menerapkan teknologi standar secara efisien menghasilkan hasil yang bermanfaat dengan penggunaan gambut sebagai solusi untuk ketahanan pangan melalui sentuhan teknologi. Dasar hukumnya adalah Peraturan Presiden tahun 2016 tentang Badan Restorasi Gambut, yang berfungsi untuk mempercepat restorasi kawasan dan mengembalikan fungsi hidrologis gambut akibat kebakaran hutan dan lahan dengan cara khusus, sistematis, terarah, terpadu, terintegrasi dan komprehensif.Kata kunci: Ketersediaan Pangan, Lahan Gambut, Teknologi АннотацияРезультаты этого исследования показывают, что проблемы в использовании торфяных технологий включают скорость преобразования сельскохозяйственных земель, расширение сельскохозяйственных земель и увеличение производства продовольственных культур, которое не является оптимальным. Хотя использование торфяных технологий – это долгосрочное решение проблемы пожаров и смога. В связи с этим  важно реализовать Постановление Правительства от 2016 года о защите и управлении торфяными экосистемами для удовлетворения основных потребностей сообщества из местных ресурсов. Обнаруженная проблема заключается в том, насколько усилиями правительства возможно повысить реализацию продовольственной достаточности за счет использования торфяников и какова правовая основа для этого. Используемый метод исследования является нормативно-юридическим с использованием вторичных данных, полученных в результате изучения литературы и проанализируемых качественным методом. Результаты и обсуждение данного исследования заключаются в том, что усилия правительства по применению стандартной технологии эффективно дают полезные результаты с использованием торфа в качестве решения для обеспечения продовольственной безопасности посредством технологического подхода. Правовой основой является Постановление Президента 2016 года об Агентстве по Восстановлению торфа, функция которого заключается в ускорении восстановления территории и восстановлении гидрологической функции торфа в результате лесных и земельных пожаров особым, систематическим, направленным, интегрированным, комплексным и всесторонним образом.Ключевые слова: наличие продовольствия, торфяники, технология